Human cytosolic sulfotransferase SULT1C4 mediates the sulfation of doxorubicin and epirubicin. Issue 2 (April 2016) - Luo, Lijun; Zhou, Chunyang; Hui, Ying; Kurogi, Katsuhisa; Sakakibara, Yoichi; Suiko, Masahito; Liu, Ming-Cheh
Abstract: Doxorubicin, an anthracycline, has been reported to be excreted in sulfate conjugated form. The current study aimed to identify the human cytosolic sulfotransferase(s) (SULT(s)) that is(are) capable of sulfating doxorubicin and its analog epirubicin, and to verify whether sulfation of doxorubicin and epirubicin may occur under metabolic conditions. A systematic analysis of thirteen known human SULTs, previously cloned, expressed, and purified, revealed SULT1C4 as the only human SULT capable of sulfating doxorubicin and epirubicin. Cultured HepG2 human hepatoma cells and Caco-2 human colon carcinoma cells were labeled with [ 35 S]sulfate in the presence of different concentrations of doxorubicin or epirubicin. Analysis of spent labeling media showed the generation and release of [ 35 S]sulfated doxorubicin and epirubicin by HepG2 cells and Caco-2 cells. Reverse transcription-polymerase chain reaction (RT-PCR) analysis revealed the expression of SULT1C4 in both HepG2 cells and Caco-2 cells. These results provided a molecular basis underlying the previous finding that sulfate-conjugated doxorubicin was excreted in the urine of patients treated with doxorubicin. Graphical abstract: